Development of a civil engineering curriculum and its impact on the quality of civil engineers - Kassim, Mohd. Azraai; Mohd. Ghazali, Mohd. Zulkifli (1995)
The practice of civil engineering is continually changing due to a number of external and internal factors. Hence, institutions offering civil engineering courses must continuously update and develop their curricula in order to respond to these new developments. This paper highlights the need for civil engineering curriculum to be continuously updated, presents some of the important changes in UTM's civil engineering curriculum and its impacts on the quality of future civil engineers.